ПОГРЕБЕННЫЕ ДОЛИНЫ ВОЛГИ (НИЖНЕЕ ПОВОЛЖЬЕ) - Свиточ А.А.; Бадюкова Е.Н. (My University, 2004)
The history of Volga valley from Pliocene till now is under consideration. Geological data of previous investigations prove that large river valley periodically appeared during all stages of new geologic time in the area of Lower Volga. The paleo-valley had migratory entry and characteristic landforms. Some large epochs may be determined: Pliocene - with deep incised valley, Akchaghylian and Apsheronian - the time of marine sediments and alluvium accumulation. During Pleistocene the erosion valleys, which were incised due to the fast decree of the Caspian Sea level, as a rule were being filled with alluvium in the periods of steady sea level. Later alluvium was being covered with marine sediments of transgression. Recent delta of Volga has little in common with ancient deltas in regard to genesis and morphology. It is typical bird-foot delta with a multitude of anabranches and channels.
Keywords: Pleistocene; Pliocene; 551.4.075(470.44/.47); Cenozoic::Quaternary::Pleistocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Кайнозой::Четвертичная::Плейстоцен